Red admiral Vanessa atalanta rubria (Fruhstorfer) (Insecta: Lepidoptera: Nymphalidae: Nymphalinae) - Donald W. Hall; Jerry F. Butler (EDIS, 2009)
EENY-446, a 4-page illustrated fact sheet by Donald W. Hall and Jerry F. Butler, is part of the Featured Creatures collection. It describes this distinctive, medium sized, brightly colored black and orange butterfly that is common throughout much of the United States — its distribution, description, life cycle and biology, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, April 2009.